No diagnostic utility of antibody patterns against Klebsiella pneumoniae capsular serotypes in patients with axial spondyloarthritis vs. patients with non-specific low back pain: a cross-sectional study. (4th July 2017) - Hermansen, LT; Loft, AG; Christiansen, AA; Munk, HL; Gilbert, L; Jurik, AG; Arnbak, B; Manniche, C; Weber, U; Østergaard, M; Pedersen, SJ; Barington, T; et al.
Abstract : Objectives : To investigate whether antibody response patterns against Klebsiella pneumoniae capsular serotypes can discriminate patients with axial spondyloarthritis (axSpA) from patients with non-specific low back pain (LBP). Method : Immunoglobulin (Ig)G and IgA antibodies against K. pneumoniae capsular serotypes K2, K26, K36, and K50 were measured, and antibody seropositivity compared between groups and analysed for patient correlation in five different groups: (a) 96 patients fulfilling the Assessment of SpondyloArthritis International Society (ASAS) classification criteria for axSpA; (b) 38 patients with either a positive magnetic resonance imaging (MRI) scan as defined by ASAS or a positive human leucocyte antigen (HLA)-B27 status plus one clinical SpA feature, characterized as 'non-axSpA'; (c) 82 non-specific LBP patients; (d) 40 healthy blood donors and (e) 43 patients with diagnosed ankylosing spondylitis (AS) served as the negative and positive control groups. Results : There was no difference in IgG and IgA seropositivity against all serotypes between the axSpA, non-axSpA, and LBP groups. No significant correlations were found between anti- Klebsiella antibodies and age, gender, HLA-B27, or high-sensitivity C-reactive protein (hsCRP). IgG seropositivity against K50 was more frequent in AS (25.6%) than in axSpA (13.5%, p < 0.05). axSpA patients with radiographic sacroiliitis and AS controls concordantly had the highest frequency of seropositivity for ≥ 2 serotypes (21%). Conclusions : The antibody patterns against K. pneumoniae serotypes K2, K26, K36, and K50 did not discriminate between early axSpA and non-specific LBP.